2017
DOI: 10.22159/ajpcr.2017.v10i12.21503
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Anredera Cordifolia (Ten.) V. Steenis Leaves Extracts and Fractions

Abstract: Objective: This study aims to determine antibacterial activity of Anredera cordifolia leaves extracts and fractions.Methods: Crude drug was extracted using two methods. First method was extraction by reflux using ethanol 96% and then fractionated by liquidliquid extraction using n-hexane and ethyl acetate. Second method was gradually extraction by reflux using n-hexane, ethyl acetate and ethanol 96%, respectively. Phytochemical screening was applied to all extracts and fractions, followed by thin-layer chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Flavonoid compounds contained in Binahong leaves had been known to form a complex with bacterial cell wall protein, damaging the cell wall and ultimately causing bacterial cell lysis [23]. Binahong leaf ethanolic extract also contains ursolic acid, which had been known to inhibit the growth of various pathogens, including S. aureus [26]. A previous study by Leliqia et al determined the minimum inhibitory concentration of Binahong leaf ethanolic extract against various Grampositive pathogens, including S. aureus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoid compounds contained in Binahong leaves had been known to form a complex with bacterial cell wall protein, damaging the cell wall and ultimately causing bacterial cell lysis [23]. Binahong leaf ethanolic extract also contains ursolic acid, which had been known to inhibit the growth of various pathogens, including S. aureus [26]. A previous study by Leliqia et al determined the minimum inhibitory concentration of Binahong leaf ethanolic extract against various Grampositive pathogens, including S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study by Leliqia et al determined the minimum inhibitory concentration of Binahong leaf ethanolic extract against various Grampositive pathogens, including S. aureus. The authors reported that ethanolic extract of Binahong leaves obtained through maceration only has bacteriostatic activity against S. aureus [26].…”
Section: Resultsmentioning
confidence: 99%
“…Steenis), one of 6000 types of plants in Indonesia, have been used for several health treatments [1]. Binahong has pharmacological effects such as anti-bacterial [2][3][4][5], anti-fungal [6], anti-aging [7], anti-diabetes [8], wound healing [9][10][11], anti-inflammatory [12], anti-oxidant [13], anti-cancer [14], anti-obesity [15] and anti-hyperuricemia [16]. Due to its pharmacological activities, binahong was potential to be developed as traditional medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Steenis, commonly known as "binahong" in Indonesia, is one of the medicinal plants that has been shown to have pharmacological activities. In addition to its antibacterial activities, binahong has been reported to have antidiabetic, antiobesity,antihyperlipidemic,vasodilator and wound healing activities (Leliqia et al 2017). Previous studies have shown that ethanolic extract of A. cordifolia leaves showed antibacterial activities against Bacillus subtilis, Escherichia coli, methicillin-resistant coagulase-negative staphylococci (MRCNS), and Pseudomonas aeruginosa (Garmana et al 2014).…”
Section: Introductionmentioning
confidence: 99%